Journeys from discomfort to comfort: how do university students experience being taught and assessed by adults with intellectual disabilities? - Feely, Michael; Garcia Iriarte, Edurne (My University, 2021)
From 2016-17, academics at a leading Irish university collaborated with a group of self- advocates with intellectual disabilities to co-design, co-deliver, and co-assess an entire disability module for third-year undergraduate social work students. There are few, if any, reports of university modules of this type, involving adults with intellectual disabilities, in the existing literature. Alongside and after the module, our group of academics and self-advocates conducted inclusive research regarding relevant stakeholders’ experiences of the initiative. This paper relates to university students’ experiences of being taught and assessed by adults with intellectual disabilities. These experiences were overwhelmingly positive with reported benefits including increased comfort around disability and greater empathy with people with people with disabilities. This said, some aspects of being taught and assessed by self-advocates with intellectual disabilities also provoked considerable anxiety among students.
PUBLISHED
Keywords: Intellectual disability; Learning disability; University; Inclusion; Health and social care professional education; Identities in Transformation; Inclusive Society; Disability; INTELLECTUAL DISABILITY; Inclusive Education